Суб’єкти адміністративних правопорушень на авіаційному транспорті - Брусакова, О. В.; Brusakova, O. V.; Оксана Брусакова (Право і безпека. – 2022. – № 3 (86). – С. 170-182, 2022)
Проведено комплексне дослідження загального та спеціальних суб’єктів адміністративних правопорушень на авіаційному транспорті. Проаналізовано міжнародно-правові акти та національне законодавство в галузі цивільної авіації. Встановлено коло суб’єктів адміністративних правопорушень на авіаційному транспорті. На підставі кваліфікаційних характеристик осіб авіаційного персоналу визначено види спеціальних суб’єктів відповідальності за адміністративні правопорушення на авіаційному транспорті, що пов’язані з порушенням польотів, з порушенням нормативно-правових актів, які регулюють діяльність авіації. Зазначено, що суб’єктами адміністративного правопорушення на авіаційному транспорті є загальний та спеціальний.

A comprehensive study of general and special subjects of administrative offenses in air transport has been conducted. The range of subjects of administrative offenses on air transport has been established. The types of special subjects of responsibility for administrative offenses in aviation transport have been determined and special subjects of responsibility for adminis-trative offenses in aviation transport related to violation of flights, violation of norms of norma-tive legal acts regulating aviation activity has been investigated.It has been proved that only individuals can be subjects of administrative liability, and both le-gal entities and individuals can be subjects of liability in the form of administrative and eco-nomic, financial, penalties and fines. For illegal actions in the field of civil aviation, legal entities and individuals are liable in accordance with the law.Based on international legal acts and documents of national legislation in the field of civil aviation, the concepts of “crew member”, “aircraft commander”, “other persons ofthe flight crew” have been analyzed. It has been found that the legal position of the aviation personnel who belong to the aircraft crew and other aviation personnel of civil aviation, as well as their rights and responsibilities, influence the determination of the composition of certain administrative offenses in air transport related to the violation of flight rules, the performance of which is in-extricably linked to a certain legal, professional, behavioral or other status of a person.It has been concluded that the subject of an administrative offense in air transport is a natural person of full legal capacity who at the time of committing the administrative offense has reached the age of sixteen (general subject). Depending on the signs of an administrative offense, a special subject may be individuals whose activities are associated with a certain legal, professional, physical, behavioural or other status, as well as officials of enterprises, institu-tions or organizations (legal entities) that carry out activities in the field of civil aviation.It has been noted that the allocation of certain types of special subjects of administrative offenses in air transport depends on the nature of their activities, which is based on the characteristics of the objective side of the offense.

Проведено комплексное исследование общего и специальных субъектов административных правонарушений на авиационном транспорте. Проанализированы международно-правовые акты и национальное законодательство в отрасли гражданской авиации. Установлен круг субъектов административных правонарушений на авиационном транспорте. На основании квалификационных характеристик лиц авиационного персонала определены виды специальных субъектов ответственности за административные правонарушения на авиационном транспорте, которые связаны с нарушением полетов, с нарушением нормативно-правовых актов, регулирующих деятельность авиации. Определено, что субъектами административного правонарушения на авиационном транспорте являются общий и специальный.
Subjects of administrative offenses on air transport
Субъекты административных правонарушений на авиационном транспорте
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративна відповідальність; administrative responsibility; административная ответственность; адміністративні правопорушення; administrative offenses; административные правонарушения; авіаційний транспорт; air transport; авиационный транспорт; спеціальний суб’єкт; special subject; специальный субъект; посадова особа; official; должностное лицо; повітряне судно; aircraft; воздушное судно